Parotid metastases from primary lung cancer: Case series and systematic review of the features - Wang, Rulan; Wang, Ting; Zhou, Qinghua (Frontiers in Oncology, 2022)
Most parotid metastases have been reported to come from the head and neck; however, cases metastasized from the lung are extremely rare. Missed diagnoses and misdiagnoses occurred quite a few times. Thus, accurately identifying the clinical features of parotid metastasis of lung cancer is important. However, current studies about this issue are mostly case reports, and little is known about the detailed and systematic aspects. We reported three cases of parotid metastases from lung cancer and then systematically searched similar cases through “Pub-Med” and “Web of Science”. Finally, twenty patients were included in the study. Eighty-five percent of which were males, and 17 patients were over 50 years old. In all cases where the smoking history were mentioned, 91% were smokers. The predominant pathological type was small cell lung cancer (SCLC, 13 patients, 65%). Fifteen combined with other site metastasis, while more than half of which were brain metastases. The survival time ranged from 3months-17years, and as for SCLCs, it was only 3months-40months. It can be concluded that clinical features, such as sex, age, smoking history, pathological types, and metastasis patterns, could provide valuable evidence for diagnosis. The lung seems to be the most common primary site of parotid metastases except for head and neck tumors. The two circumstances, SCLC coexisting with Warthin's tumor and parotid small cell carcinoma with lung metastasis, should be interpreted with caution in the differential diagnosis. For cases presented as SCLC, more aggressive strategies, such as chemotherapy with immunotherapy and maintenance therapy, may be more suitable. Due to the greater tendency of brain metastasis in such diseases, whole-brain radiation therapy, stereotactic radiosurgery or prophylactic cranial irradiation should be applied to corresponding patients in time. Additionally, lung cancer parotid metastasis may be a marker of poor prognosis.